How and why neurons die in Alzheimer's disease? - De Strooper, Bart (Henry Stewart Talks, 2024)
Alzheimer’s disease, Amyloid, In vivo disease model, Dug development, MEG3, Necroptosis, Neuronal cell death, Pathogenesis, Stem cell, Tau pathology.